Introduction to Applied Stress Testing - Cihak, Martin (Washington, D.C. : International Monetary Fund, 2007)
Stress testing is a useful and increasingly popular, yet sometimes misunderstood, method of analyzing the resilience of financial systems to adverse events. This paper aims to help demystify stress tests, and illustrate their strengths and weaknesses. Using an Excel-based exercise with institution-by-institution data, readers are walked through stress testing for credit risk, interest rate and exchange rate risks, liquidity risk and contagion risk, and are guided in the design of stress testing scenarios. The paper also describes the links between stress testing and other analytical tools, such as financial soundness indicators and supervisory early warning systems. Furthermore, it includes surveys of stress testing practices in central banks and the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet